Height Estimation Using Arm Span and Hand Length Measurements - Satyal, Biswas; Poudel, Abhishek (Journal of Nepalgunj Medical College, 2017)
Introduction: Arm span and hand length can be used for the estimation of an individual stature. Arm span, hand length, foot length, head circumference etc. have been proved to be useful to correctly estimate the height of a person. It can be useful in various medico legal purposes. Objectives: The present study was undertaken to find the correlation between the arm-span and hand length with the standing height of both males and females and to derive regression equations for estimation of their height. Materials and Method: This cross sectional type of descriptive study was carried out with a total number of 200 Nepalese medical students consisting of 120 male and 80 female aged between 18 to 24 years. Stature, arm span and hand length were measured directly from the subjects by using anthropometric technique by a measuring tape and a spreading caliper. The data taken were statistically analyzed by computation. The relationship between body height, arm span and hand length were determined using simple correlation coefficients. Result and Conclusion: In this study, the correlation between the arm-span and hand length with the standing height of both males and females was found to be an accurate predictor of the height and regression formulae were derived for calculating the height of male or female with the arm-span and hand length.